Modeled impact of the COVID-19 pandemic and associated reduction in adult vaccinations on herpes zoster in the United States. Issue 1 (31st December 2022) - Curran, Desmond; La, Elizabeth M.; Salem, Ahmed; Singer, David; Lecrenier, Nicolas; Poston, Sara
ABSTRACT: Due to COVID-19, vaccinations dropped in 2020 and 2021. We estimated the impact of reduced recombinant zoster vaccine (RZV) use on herpes zoster (HZ) cases, complications, and quality-adjusted life-year (QALY) losses among older adults. Various scenarios were compared with Markov models using data from national sources, clinical trials, and literature. Missed series initiations were calculated based on RZV distributed doses. In 2020, 3.9 million RZV series initiations were missed, resulting in 31, 945 HZ cases, 2, 714 postherpetic neuralgia cases, and 610 lost QALYs. Scenarios further projected disease burden increases if individuals remain unvaccinated in 2021 or the same number of initiations are missed in 2021. Health professionals should emphasize the importance of vaccination against all preventable diseases during the COVID-19 era.